Young driver perceptions of police traffic enforcement and self-reported driving offences. Issue 4 (21st November 2016) - Bates, Lyndel Judith; Scott-Parker, Bridie; Allen, Siobhan; Watson, Barry
Abstract : Purpose: Road policing is a key method used to improve driver compliance with road laws. However, the authors have a very limited understanding of the perceptions of young drivers regarding police enforcement of road laws. The paper aims to address this gap. Design/methodology/approach: Within this study 238 young drivers from Queensland, Australia, aged 17-24 years ( M =18, SD=1.54), with a provisional (intermediate) driver's licence completed an online survey regarding their perceptions of police enforcement and their driver thrill-seeking tendencies. This study considered whether these factors influenced self-reported transient (e.g. traveling speed) and fixed (e.g. blood alcohol concentration) road violations by the young drivers. Findings: The results indicate that being detected by police for a traffic offence, and the frequency with which they display P-plates on their vehicle to indicate their licence status, are associated with both self-reported transient and fixed rule violations. Licence type, police avoidance behaviors and driver thrill seeking affected transient rule violations only, while perceptions of police enforcement affected fixed rule violations only. Practical implications: This study suggests that police enforcement of young driver violations of traffic laws may not be as effective as expected and that the authors need to improve the way in which police enforce road laws for young novice drivers. Originality/value: This paper identifies that perceptions of police enforcement by young drivers does not influence all types of road offences.